Strength Performance of Mortar Containing Bagasse Ash and Rice Husk Ash as Cementitious Material - Hyder, Sarfraz; Ali, Sajjad; Ali, Suhail; Narejo, Rukhsar Ali; Shahidan, Shahiron (Journal of Structural Monitoring and Built Environment, 2022)
The use of cement as a main binding material in the field of civil engineering is no doubt at the next level due to growth in urbanization. It is mainly used to make cement mortar, concrete, and other composite construction material. The extensive use of OPC in the construction industry has caused increment in the production of CO2 at atmosphere. This has deteriorated the environment and has urged everyone to study and research the sustainable progress by using different waste products as replacement in concrete and mortar. Therefore, the purpose of this study was to investigate the strength performance of cement mortar containing Sugarcane Bagasse Ash (SCBA) and Rice Husk Ash (RHA) as a Cementitious Material. In this study, we have substituted the cement with different percentages i.e., 0%, 5%, 10% and 15% of both sugarcane bagasse ash (SCBA) and rice husk ash (RHA) to obtain sustainable mortar. Flowability, Density and compressive strength were examined by casting 36 standard cubes of 50mm size and cured for 3, 7 and 28 days. Test outcomes indicated that the flowability of mortar paste kept on decreasing with the increase in partial replacement by SCBA and RHA. As we have fixed the water cement ratio for all type of mix i.e., 0.5. From the outcomes of Density and Compressive Strength of Cubes cured in plain water, we come to know that as % replacement was increasing the density and compressive strength of cubes cured was reducing. For Compressive Strength, it was found that at each specified day, the compressive strength of cubes up to 10% replacement has given a reasonable value but intensely decreased at 15% replacement. At 5% replacement of both SCBA and RHA on 28th day test it was pointed that compressive strength of cubes has the highest values for all % of replacement.